Gender and social computing interactions, differences, and relationships - Romm-Livermore, Celia, 1954- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book provides an overview of the major questions that researchers and practitioners are addressing, outlining possible future directions for theory development and empirical research on gender and computing"--Provided by publisher.